2017
DOI: 10.2147/dddt.s118154
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the long-term efficacy and safety of generic Tacrobell with original tacrolimus (Prograf) in kidney transplant recipients

Abstract: This study aimed to evaluate the long-term efficacy and safety of a generic tacrolimus (Tacrobell [TCB]) compared to the original tacrolimus (Prograf [PGF]) in kidney transplant recipients. In this retrospective observational study, we analyzed the data from 444 patients who took TCB as a first-line immunosuppressive drug and 245 patients who took PGF. The 5-year graft survival rate was 92% for patients in the PGF group and 97% for patients in the TCB group, respectively. Cox proportional hazards for a one-sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…). Only one study after KT conversion found a significant difference between generic and innovator Tac favoring innovator Tac , while one in KT de novo found a significant benefit of generic Tac . Two further crossover studies including 103 patients after KT and 36 patients after LT conversion did not report any BPAR event.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…). Only one study after KT conversion found a significant difference between generic and innovator Tac favoring innovator Tac , while one in KT de novo found a significant benefit of generic Tac . Two further crossover studies including 103 patients after KT and 36 patients after LT conversion did not report any BPAR event.…”
Section: Resultsmentioning
confidence: 95%
“…A total of 390 publications were excluded during abstract screening. After the elimination of preliminary reports (2), case reports (3), reviews (25), and studies without a control group (16), 17 studies met the inclusion criteria (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study of kidney transplant patients also found no difference in adverse events (cardiovascular events, cerebrovascular events, malignancies, newly diagnosed onset of diabetes, and infectious events). 14 These results indicate that TCB is as safe as PGF.…”
Section: Discussionmentioning
confidence: 80%